Competences development and turnover intentions: the serial mediation effect of perceived internal employability and affective commitment - Moreira, Ana (2020)
Purpose – This study aims to explore the serial mediation effect of perceived internal employability and affective commitment in the relationship between the organisational practices of competences development and turnover intentions. Design/methodology/approach – The methodology was quantitative and is based on a survey with a sample of 313 participants, all of whom were employed in several organisations located in Portugal. Findings – A significant and negative effect of organisational practices of competences development, perceived internal employability and affective commitment on turnover intentions was verified. A total serial mediation effect was also found from perceived internal employability and affective commitment in the relationship between organisational practices of competences development (i.e., training, individualised support and functional rotation) and turnover intentions. Practical implications – These practices should be developed by leaders of organisations in order that employees feel that the organisation is investing in their development, which can lead to an increase in their emotional attachment towards the organisation and consequently increase their desire to stay in the organisation. Originality/value – This study makes two important contributions. First, it confirms the existence of a significant and negative relationship between perceived internal employability and turnover intentions. Second, it proves the existence of a total serial mediation effect of perceived internal employability and affective commitment in the relationship between organisational practices of competences development and turnover intentions.